2016
DOI: 10.1186/s13059-016-0921-4
|View full text |Cite
|
Sign up to set email alerts
|

Talking about cross-talk: the immune system and the microbiome

Abstract: A report on the first EMBO conference entitled “Next Gen Immunology—From Host Genome to the Microbiome: Immunity in the Genomic Era”, held at the Weizmann Institute of Science, Israel, 14–16 February, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Several studies have demonstrated a close interaction between microbiota and innate immune-cell components [for reviews, see [196][197][198][199][200]. The individual composition of the microbiota thus adds another layer of complexity in the regulation and function of the innate immune system [196,[201][202][203][204] in both health and disease [196,205,206] . Seminal findings support an impact of the microbiome on (i) innate immune cells (neutrophils [36,207] , DCs [208][209][210][211][212][213][214][215][216][217] , macrophages [218][219][220] , ILCs [198,[221][222][223][224][225] , NK cells [226] , and NKT cells [227] ), (ii) the complement system [228] , and (iii) defensins [196,229,230] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a close interaction between microbiota and innate immune-cell components [for reviews, see [196][197][198][199][200]. The individual composition of the microbiota thus adds another layer of complexity in the regulation and function of the innate immune system [196,[201][202][203][204] in both health and disease [196,205,206] . Seminal findings support an impact of the microbiome on (i) innate immune cells (neutrophils [36,207] , DCs [208][209][210][211][212][213][214][215][216][217] , macrophages [218][219][220] , ILCs [198,[221][222][223][224][225] , NK cells [226] , and NKT cells [227] ), (ii) the complement system [228] , and (iii) defensins [196,229,230] .…”
Section: Discussionmentioning
confidence: 99%
“…The immune system functions in many axes. Crosstalk between the neutrophils and lymphocytes (37) as well as the microbiome and the immune system is a common phenomenon (38). Also, stimulation of the immune system with these vaccines would efficiently build a defense, crosstalk, and "chaos" (39) in the frontline, which would strengthen the immune system for SARS-Co-2 infections.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…They play a role in the development of mucosal and systemic immunity and are also involved in host liver disease (Lu et al, 2011; Qin et al, 2014; Chen et al, 2016). Intestinal dysbiosis not only disturbs intestinal immune homeostasis but can also cause immune dysfunction of other non-enteric organs (Jiang et al, 2011; Smolinska and O’Mahony, 2016; Zeevi et al, 2016), which is associated with the induction and progression of liver damage (Garcia-Tsao and Wiest, 2004; Ren et al, 2013). Although liver disease is not necessarily a consequence of these disruptions, diseases of the liver always result in downstream intestinal microbiome and immune dysbiosis (Qin et al, 2014; Lv et al, 2016).…”
Section: Introductionmentioning
confidence: 99%